Visitors' recreational & leisure experiences in urban river corridors? a case study of Hutuo River in Shijiazhuang, China - Lin, Shi; Maruthaveeran, Sreetheran; Mohd Yusof, Mohd Johari (Elsevier, 2024)
Various physical environmental factors influence the recreational experience of urban river corridors, and understanding visitors' perceptions of these factors holds significant implications for promoting the health and well-being of urban residents. This study specifically focuses on the Hutuo River corridor in Shijiazhuang, China, and conducted a semi-structured questionnaire survey with 620 participants. The findings reveal that visitors mainly come here to socialize with family and friends in a natural environment and escape the city's hustle and bustle. Safety, management and maintenance, and overall conditions are the primary features visitors are concerned about in their experience. When addressing usage constraints, visitors highlight accessibility issues, including traffic congestion and overcrowding. Additional limitations encompass deficiencies in physical facilities, such as shortages of shared bicycles, convenience amenities, fitness facilities, and services catering to vulnerable groups. Moreover,challenges include unavailable toilet services and insufficient shaded areas along the riverbanks. Sociodemographic attributes such as gender, age, marital status,education level, monthly income, and residential distance significantly influence the recreational experience of urban river corridors, emphasizing the importance of considering diversity in urban planning and design. By comprehensively exploring the dynamics of urban river corridor utilization from a social-ecological perspective, our study's findings offer insights relevant to future design and maintenance endeavors.